The cross-cultural reflective model for post-sojourn debriefing. Issue 4 (4th July 2018) - Dressler, Roswita; Becker, Sandra; Kawalilak, Colleen; Arthur, Nancy
ABSTRACT: Reflective writing is a practice often encouraged in study abroad programs. Reflection can be facilitated through experiential learning, but little research is available on how to guide or structure-related learning activities. In this article, we discuss the Cross-cultural Reflection model (CCR), which emerged through our own process of researching three commonly used models for reflective writing. We document our procedure for researching, creating, testing, and modifying the CCR model, before and after using it with students in a post-sojourn debriefing workshop. In the discussion, we examine which aspects of the models examined informed the CCR model and which elements we introduced as a result of working with the models in two research retreats. The sharing of the process is intended to inform practices of reflective writing in post-sojourn debriefing to enhance international experiences, programmes, and practices.